2022
DOI: 10.3390/jof8090965
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of the Fluoroquinolone, Levofloxacin, by the White-Rot Fungus Coriolopsis gallica

Abstract: This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 92 publications
0
7
0
Order By: Relevance
“…Similarly, sulphonamide drugs like sulfadiazine, sulfamethazine and sulfamethoxazole are also among the antibiotics and were degraded individually by various types of microorganisms ( Mulla et al, 2016c , Mulla et al, 2018 , Mulla et al, 2023 , Wang et al, 2023a ). Moreover, there are reports on medicines like ciprofloxacin, tetracycline, levofloxacin (Fluoroquinolone), carbamazepine and diclofenac were degraded/removed by microorganisms ( Ben Ayed et al, 2022 , Chen et al, 2022b , Shah et al, 2022 , Wang et al, 2023b , Wojcieszyńska et al, 2023 ). Hence, various researchers are looking alternative ways like plant based molecules to control such organisms’ growth.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, sulphonamide drugs like sulfadiazine, sulfamethazine and sulfamethoxazole are also among the antibiotics and were degraded individually by various types of microorganisms ( Mulla et al, 2016c , Mulla et al, 2018 , Mulla et al, 2023 , Wang et al, 2023a ). Moreover, there are reports on medicines like ciprofloxacin, tetracycline, levofloxacin (Fluoroquinolone), carbamazepine and diclofenac were degraded/removed by microorganisms ( Ben Ayed et al, 2022 , Chen et al, 2022b , Shah et al, 2022 , Wang et al, 2023b , Wojcieszyńska et al, 2023 ). Hence, various researchers are looking alternative ways like plant based molecules to control such organisms’ growth.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this fact, C. gallica was also shown to degrade many pollutants, including dyes [ 7 , 21 ], hydrocarbons [ 29 ], phenols, and bisphenol A [ 30 ]. Recently, C. gallica was shown to be able to degrade antibiotics [ 31 ]. In the same work, proteomic analysis showed the presence of one major secreted laccase, although there were several laccase genes in the genome.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in the 1990s, the ability of several wood-rotting fungi, including Irpex lacteus , Gloeophyllum striatum or Phanerochaete chrysosporium, among others, to degrade enrofloxacin was first described [ 154 ]. Thereafter, the ability of other fungi, such as Clitocybe odora , Coriolopsis gallica, Cyathus stercoreus, Irpex lacteus , Xylaria longipes or others, to degrade or modify quinolones has been largely described [ 155 , 156 , 157 , 158 ]. Of note, the resulting metabolites may retain a degree of antibacterial activity, which varies between processed quinolones and fungi species [ 156 ].…”
Section: Quinolone Inactivation/modificationmentioning
confidence: 99%
“…Nevertheless, the role of enzymes such as cytochrome P450, or those possessing laccase-like and peroxidase-like activity, has been explored [ 155 , 156 , 159 ]; of note, the two latter types of enzymes are considered ligninolytic enzymes [ 160 ], in agreement with the apparent facility of wood-rooting fungi to degrade or modify quinolone. Along this line, a recent study analyzing the ability of Coriolopsis gallica to degrade levofloxacin suggested that enzymes with laccase-like and peroxidase-like activity may play a role due to their prevalence in fungi secretome [ 155 ]. Similarly, the chloroperoxidase of Leptoxyphium fumago (formerly Caldariomyces fumago ) is also able to degrade norfloxacin [ 161 ].…”
Section: Quinolone Inactivation/modificationmentioning
confidence: 99%